Pigeonpea in social forestry - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
ICRISAT's Genetic Resources Unit, together with the Kenya Agricultural Research Institute, have launched a programme in eastern Africa to evaluate ICRISAT's pigeonpea germplasm. The plant has been stud fed in its area of origin and adaptation in...